2009
DOI: 10.1007/s10803-009-0808-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Symbolic Relationships in Autism Spectrum Disorders: A Deficit in the Identification of Temporal Co-occurrence?

Abstract: Individuals with Autism spectrum disorders (ASD) experience difficulties understanding the non-verbal cues conveyed by others that provide symbolic information about relationships between self, other, and environmental events. This study examined whether these difficulties reflect underlying problems in the identification of temporal co-occurrence, or in memorial, associative, or inference skills. The performance of a group of adolescents with ASD was compared to that of typically developing children and adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These include deficits in executive functions [17–19], inner speech [20], cognitive control over inhibition [21], mirror neurons [22], action monitoring [23], procedural and implicit learning [24, 25], consolidation of experiences [26], prioritizing dynamic stimuli [27], relational processing [28], attentional windows [29], complex information processing [30], formulating and using higher-order rules [31], hierarchical organization in processing information [32], diachronic thinking [33], and temporal cooccurrence, integration, and binding [34, 35]. It has also been suggested that autism is affected by stimulus overselectivity [36], hypersystemising [37], and a greater inference in the local-to-global direction than in the global-to-local one [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include deficits in executive functions [17–19], inner speech [20], cognitive control over inhibition [21], mirror neurons [22], action monitoring [23], procedural and implicit learning [24, 25], consolidation of experiences [26], prioritizing dynamic stimuli [27], relational processing [28], attentional windows [29], complex information processing [30], formulating and using higher-order rules [31], hierarchical organization in processing information [32], diachronic thinking [33], and temporal cooccurrence, integration, and binding [34, 35]. It has also been suggested that autism is affected by stimulus overselectivity [36], hypersystemising [37], and a greater inference in the local-to-global direction than in the global-to-local one [38].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this general link between autism and context, research has found deficits with those with autism in the processing of context for social cues [35], face processing [47], memory [48, 49], perceptual groupings [50], distinguishing essential from variable aspects in event schemas [51], and also in the skills of generalizing from structured settings to more naturalistic ones which may contain unpredictable and context-dependent interpretational elements [52]. This impaired contextual processing in autism has also been proposed to affect the production and comprehension of language in regard to homophone pronunciation [5355], lexical ambiguity [56], sentence understanding [53, 55], semantic incongruity detection [5759], prosody production and comprehension [60, 61], metaphor and metonymy appreciation [62], irony [63], discourse continuity [64], and communication pragmatics [6567].…”
Section: Introductionmentioning
confidence: 99%
“…In the human brain, visual information from one side of the visual field is processed by the contralateral hemisphere. Schematically, data are transmitted to successive cortical maps, 52 in a serial flow with modulatory recurrent connections. The processing of information in Event-related potentials are EEG-recordable correlates of motor or cognitive events.…”
Section: Overview Of the Visual Systemmentioning
confidence: 99%
“…Symptoms of autismconsist in difficulties with oral communication, resulting in fewer attempts towards communication with the caregiver. During later development and adult life, the most frequent behavioural symptoms of autism, collectively called autistic behaviour, are difficulties with symbolic thought, restricted and repetitive behaviour, associated with or resulting in low interaction with the social environment[52,53].…”
mentioning
confidence: 99%